2023
DOI: 10.1021/acsnano.3c05869
|View full text |Cite
|
Sign up to set email alerts
|

High Entropy Sulfide Nanoparticles as Lithium Polysulfide Redox Catalysts

M. J. Theibault,
Connor R. McCormick,
Shuangyan Lang
et al.

Abstract: The polysulfide shuttle contributes to capacity loss in lithium–sulfur batteries, which limits their practical utilization. Materials that catalyze the complex redox reactions responsible for the polysulfide shuttle are emerging, but foundational knowledge that enables catalyst development remains limited with only a small number of catalysts identified. Here, we employ a rigorous electrochemical approach to show quantitatively that the lithium polysulfide redox reaction is catalyzed by nanoparticles of a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…As a result, the high-entropy sulfide exhibited superior catalytic properties than any constituent metal sulfides in both discharge and charge stages. It was noteworthy that although GuGaS 2 and CuInS 2 had catalyzed the reduction reaction, no metal sulfides catalyzed the oxidation reaction, and the high-entropy sulfide showed significantly improved oxidation kinetics due to the synergistic interaction between the components of the high-entropy sulfide [ 109 ]. Qiao designed high-entropy oxide composed of highly dispersive Ni, Mg, Cu, Zn and Co, which exposed abundant active sites, and could strong anchor LiPSs with Li–O and S–Ni bonds and catalyze LiPSs conversion of (Fig.…”
Section: Engineering Tmcs Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the high-entropy sulfide exhibited superior catalytic properties than any constituent metal sulfides in both discharge and charge stages. It was noteworthy that although GuGaS 2 and CuInS 2 had catalyzed the reduction reaction, no metal sulfides catalyzed the oxidation reaction, and the high-entropy sulfide showed significantly improved oxidation kinetics due to the synergistic interaction between the components of the high-entropy sulfide [ 109 ]. Qiao designed high-entropy oxide composed of highly dispersive Ni, Mg, Cu, Zn and Co, which exposed abundant active sites, and could strong anchor LiPSs with Li–O and S–Ni bonds and catalyze LiPSs conversion of (Fig.…”
Section: Engineering Tmcs Catalystsmentioning
confidence: 99%
“…In addition, the chemical and structural stability of high-entropy materials in the charging and discharging process of LSBs should be considered. It was found that the copper in Zn 0.30 Co 0.31 Cu 0.19 In 0.13 Ga 0.06 S was leached out as an ionic species, accompanied with the smaller particles and lower crystallinity of high-entropy sulfide, gives a good indication that stabilizing cations could prolong the life of catalysts and improve the capacity retention ability [ 109 ]. Furthermore, the significant lattice distortion is also one of the key factors for the excellent catalytic performance of high-entropy materials.…”
Section: Engineering Tmcs Catalystsmentioning
confidence: 99%
“…[26][27][28] Moreover, the inherent electronic/ion insulation, shuttle effect, growth of lithium dendrites, volume expansion, and other issues of polysulfides also affect the performance of LiÀ S batteries, especially under high sulfur loads, these problems become more severe, leading to rapid capacity decay of LiÀ S batteries. [29][30][31][32][33] Therefore, well-designed electrodes with the ability to accelerate charge transfer, suppress shuttle effects, and enhance conversion kinetics are crucial for achieving the practical application of high energy density LiÀ S batteries. [34][35][36][37][38] Reasonably designing efficient media and integrating them into batteries is a promising method for constructing high energy density LiÀ S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…With elaborate structure modulation, considerable hosts possessing high active sites, such as metals, oxides, sulfides, selenide, , and carbides, , have exhibited high catalytic activity toward the conversion of the sulfur species. In addition, many composite catalysts could also enhance the conductivity, retard the volume fluctuation of the cathode, and provide chemical and physical limitations for LiPS. ,, Particularly, some heterostructures and amorphous hosts with various catalytic sites show good catalytic capability for the bidirectional sulfur conversion reactions. ,, However, two critical issues associated with the catalytic hosts remain to be solved to further improve the performance of the sulfur cathodes, which are fabricated with a high sulfur content and high areal loading to meet the practical standards.…”
Section: Introductionmentioning
confidence: 99%